Disparities Analysis of Employment - A Dynamic Shift Share Approached - Rita Indrawati, L; Retno Sugiharti, R (KnE Social Sciences, 2018)
Naturally, regional disparities are caused by differences in regional characteristics and the degree of local sensitivity in responding the changes of business cycles. Therefor industrial growth and employment growth resulted from the regional competitiveness will be different in each region. The aims of this research was analyze the disparities in regional employment. By using Indonesian labor database retrieved from BPS (Badan Pusat Statistik- Indonesian Central Burau of Statistic), the object of these research object was 34 city/district in Central Java Province 2009 to 2013. Dynamic shift-share analysis proposed by Barff & Knight (1988) was used to calculate the extent of the difference in employment growth between each region and the national average. The regional industrial structure, or to a residual element from its calculate on can be interpreted as indicating the locational advantages of each regional economy. Disparities in employment occur in the Central Java Province. The growth rate of employment in urban areas is slower than in the districts. Finally, the positive value on the residual mix coefficient indicates that overall 35 districts/cities in the Central Java region have high competitiveness prospects so that employment will grow in line with increasing competitiveness. Keywords: disparities, employment, dynamic shift-share